PENGARUH TEBAL SELIMUT BETON NORMAL PADA LAJU KOROSI BAJA TULANGAN - Pramudiyanto Pramudiyanto; A. Triwiyono A. Triwiyono; HRC Priyosulistyo (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2011)
Corrosion of steel reinforcement is the main cause of deterioration andpreliminary failure of reinforced concrete construction. The effect is the large amountof funding to repair, restore and replace the broken part. The aim of this research isto figure out the corrosion process on the reinforcement of concrete construction withlocal aggregate in the salt water environment. The specific aim is to find out thecorrosion rate of steel reinforcement having concrete compression strength between25 MPa to 30 MPa.The DC Electrochemical Test Method with impressed current technique was used inthis research. The test is using cylinder with various diameter. The reinforcementsteel is placed in the center of cylinder cross section to make a condition of differentcover thickness. The test was conducted 45 days non-stop, observing specimen’spotential change and crack pattern. The corrosion rate and corrosion current density(Icorr) were compute using weight loss of steel. The carbonation test using bufferphenolphthalein was also conducted in this research.The result shows that there’re a downstream trend of corrosion rate and corrosioncurrent density to the concrete cover’s thickness. The corrosion rate of ∅1.25”, ∅3”,∅5” and ∅6” specimens as follow: 4.440981 mm/yr, 1.63395 mm/yr, 0.026253mm/yr and 0.00 mm/yr. The corrosion current density (Icorr) of ∅1.25”, ∅3”, ∅5” and∅6” specimens as follow: 0.000382446 mA/cm2, 0.000141 mA/cm2, 2.2x10-6 mA/cm2and 0.00 mA/cm2.The potential change’s profile will goes down according to the timeof test. The graph of potential change to the time forming a curved line until a timewhen the line becomes straight. The crack pattern started from the region betweenthe submerge and the dry region, then move to the entire part of specimen. Thecarbonation was dominated by corroded specimen.Keyword: corrosion of concrete reinforcement, concrete cover thickness,carbonation, impressed current technique